Properties of Si3N4/SiC composites produced via spark plasma sintering - Taslicukur, Zeynep; Sahin, Filiz Cinar; Kuskonmaz, Nilgun (CARL HANSER VERLAG, 2012)
Si3N4 ceramics reinforced with SiC particles were fabricated via spark plasma sintering at 1 650 degrees C under 40 MPa pressure. AlN and Y2O3 were used as sintering additives. The purpose of this work was to study the influence of SiC powders on the properties of Si3N4/SiC composites. The microstructure, phase composition, and mechanical properties of the composites were investigated. It was found that mechanical properties of the composites improved, the a alpha-beta transformation and grain growth of beta-Si3N4 were inhibited and the equiaxed grain increased due to the increase of SiC(w).
Keywords: Si3N4; SiC; Spark plasma sintering; Mechanical properties; MECHANICAL-PROPERTIES; MICROSTRUCTURE; CERAMICS; FABRICATION; Metallurgy & Metallurgical Engineering